IMPLEMENTASI PEMASARAN MEDIA SOSIAL INSTAGRAM @GYUGYUGANK DALAM MENINGKATKAN KESADARAN MEREK - Azalia Nediva Kuntjoro; Elfira Annisa Sastra; Sam'un Jaja Raharja; Lina Auliana; Raden Marsha Aulia Hakim (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of conducting this research is to examine the social media marketing of Instagram @gyugyugank in enhancing brand awareness. The research is conducted using a qualitative method and analyzed using a descriptive method, with data sources from direct interviews with Gyu Gyu Gank employees and consumers as followers of the @gyugyugank Instagram account, along with literature studies. The results of this research indicate that Gyu Gyu Gank pays close attention to social media marketing strategies that impact brand awareness improvement. Gyu Gyu Gank employs various strategies to manage the Instagram social media account to enhance brand awareness, which includes levels of unawareness of the brand, brand recognition, brand recall, and brand top-of-mind. Keywords: Social Media Marketing, Instagram, Brand Awareness